The Influence of Deuterium on the Properties of Pharmaceutical Substances (Review) - A. V. Syroeshkin; T. E. Elizarova; T. V. Pleteneva; E. V. Uspenskaya; O. V. Levitskaya; I. A. Zlatskiy; T. V. Maksimova (Разработка и регистрация лекарственных средств)
Introduction. The study discusses the hydrogen isotope 2H effect on the biological activity of pharmaceutical substances.Text. Two aspects of the deuterium effect on the properties of active pharmaceutical ingredients and excipients are considered. The first one involves the use of deuterated substances, new compounds or substituted counterparts. Replacing protium with deuterium is used to reduce the rate of biotransformation. The kinetic isotope effect (KIE), expressed in a decrease in the rate of biotransformation as a result of deuteration, allows us to predict the rapid development of new directions in the development of pharmaceuticals. With the same therapeutic effect, an improvement in pharmacokinetic characteristics, a decrease in toxicity, a blocking of the epimerization of optically active substances, a change in the mechanisms of action are observed. The second aspect of the deuterium effect is associated with an increase in KIE of known pharmaceutical substances in aqueous solutions with a deuterium/protium ratio (D/H) lower than in natural water. For the first time, dose-response diagrams for deuterium demonstrate identity with essential microelements. There is a safety zone for the certain D/H relationship, beyond which the organism's vitality decreases. Improved kinetic characteristics are demonstrated for molecular level and for biological objects of various hierarchical levels. In particular, they include the possibility of increasing the dissolution rate of substances, the influence on the processes of mutarotation and the optical activity of chiral substances, the degree of accumulation of necessary elements in medicinal plants, and other processes.Conclusion. The results make it possible to predict the mechanisms of deuterium influence on the biochemical transformations of pharmaceutical substances in the body.